Impairment of the class IIa bacteriocin receptor function and membrane structural changes are associated to enterocin CRL35 high resistance in Listeria monocytogenes - Masias, Emilse; Dupuy, Fernando G.; da Silva Sanches, Paulo Ricardo; Farizano, Juan Vicente; Cilli, Eduardo; Bellomio, Augusto; Saavedra, Lucila; Minahk, Carlos (Biochimica et biophysica acta. General subjects, 2017)
Enterocin CRL35 is a class IIa bacteriocin with anti-Listeria activity. Resistance to these peptides has been associated with either the downregulation of the receptor expression or changes in the membrane and cell walls. The scope of the present work was to characterize enterocin CRL35 resistant Listeria strains with MICs more than 10,000 times higher than the MIC of the WT sensitive strain. Listeria monocytogenes INS7 resistant isolates R2 and R3 were characterized by 16S RNA gene sequencing and rep-PCR. Bacterial growth kinetic was studied in different culture media. Plasma membranes of sensitive and resistant bacteria were characterized by FTIR and Langmuir monolayer techniques. The growth kinetic of the resistant isolates was slower as compared to the parental strain in TSB medium. Moreover, the resistant isolates barely grew in a glucose-based synthetic medium, suggesting that these cells had a major alteration in glucose transport. Resistant bacteria also had alterations in their cell wall and, most importantly, membrane lipids. In fact, even though enterocin CRL35 was able to bind to the membrane-water interface of both resistant and parental sensitive strains, this peptide was only able to get inserted into the latter membranes. These results indicate that bacteriocin receptor is altered in combination with membrane structural modifications in enterocin CRL35-resistant L. monocytogenes strains. Highly enterocin CRL35-resistant isolates derived from Listeria monocytogenes INS7 have not only an impaired glucose transport but also display structural changes in the hydrophobic core of their plasma membranes. [Display omitted] •Two Listeria monocytogenes isolates resistant to enterocin CRL35 were characterized.•Both resistant isolates had impaired glucose transport, which is indicative of alteration of the mannose-PTS complex.•Resistant isolates could be distinguish from each other based on cell wall differences.•R2 and R3 isolates displayed major changes in the membrane lipids.•Enterocin CRL35 was able to bind to the membrane surface of resistant cells but it could not get inserted into these membranes.